Keberadaan Sanksi Adat Terhadap Penegakan Hukum Pidana Dalam KUHP Baru - Hutabarat, Priskila; Siregar, Elizabeth; Haryadi, Haryadi (PAMPAS: Journal of Criminal Law, 2025)
The enactment of Law Number 1 of 2023 concerning the Criminal Code as a renewal of the current criminal law has a very significant difference. One of them is the recognition of customary law and the application of customary sanctions as well as the expansion of the principle of legality. This study aims to analyze existence customary sanctions against criminal law enforcement through the expansion of the principle of legality in the New Criminal Code. The research method used in writing this thesis is normative juridical, meaning analyzing a legal problem through laws and regulations, literature and other reference materials. This thesis uses several approaches, including the statute approach, the conceptual approach, and the historical approach. This study discusses the regulation of customary sanctions on criminal law enforcement and the concept of the principle of legality in the New Criminal Code that affects customary sanctions in the criminal justice system. The results of this study are about the regulation of customary law, customary sanctions, and the expansion of the principle of legality in Law Number 1 of 2023 concerning the Criminal Code. There is a potential for the loss of cultural values of customary law communities in this Law, the expansion of the principle of legality that accommodates customary law into Regional Regulations limiting the space for customary law movement, and the application of customary sanctions which is still ambiguous because there are no regulations related to the strength of customary institution decisions. Judges in their rulings as a form of indirect law enforcement must add customary sanctions as an additional crime so that the cultural value of indigenous peoples is not lost. Abstrak Ditetapkannya Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana sebagai pembaharuan terhadap hukum pidana saat ini memiliki perbedaan yang sangat signifikan. Salah satunya adalah diakuinya hukum adat dan berlakunya sanksi adat serta adanya perluasan asas legalitas. Penelitian ini bertujuan untuk menganalisis keberadaan sanksi adat terhadap penegakan hukum pidana melalui perluasan asas legalitas dalam KUHP Baru. Metode penelitian yang digunakan dalam penelitian ini yakni yuridis normatif artinya menganalisis suatu permasalahan hukum melalui peraturan perundang-undangan, literatur dan bahan referensi lainnya. Penelitian ini menggunakan beberapa pendekatan, anatar lain pendekatan Perundang-undangan (statute approach), pendekatan konseptual (conseptual approach), dan pendekatan historis (historical approach). Penelitian ini membahas pengaturan sanksi adat terhadap penegakan hukum pidana dan konsep asas legalitas dalam KUHP Baru yang mempengaruhi sanksi adat dalam sistem peradilan pidana. Hasil dari penelitian ini tentang pengaturan hukum adat, sanksi adat, dan perluasan asas legalitas dalam Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana. Terdapat potensi hilangnya nilai-nilai kultural masyarakat hukum adat dalam Undang-Undang ini, perluasan asas legalitas yang mengakomodasi hukum adat kedalam Peraturan Daerah membatasi ruang gerak hukum adat, serta penerapan sanksi adat yang masih rancu karena belum adanya regulasi terkait kekuatan putusan Lembaga Adat.Hakim dalam putusannya sebagai bentuk penegakan hukum secara tidak langsung harus menambahkan sanksi adat sebagai pidana tambahan agar nilai nilai kultural masyarakat adat tidak hilang.